Sistem Pendukung Keputusan untuk Menentukan Pemberian Beasiswa di STMIK Atma Luhur - Magdalena, Hilyah (Jurnal Buana Informatika, 2012)
Abstract. Top of FormEconomic conditions is one obstacle in implementing education especially higher education. This limitation can be overcome by granting scholarships. With the scholarship students who have excellent academic ability can continue their education. In STMIK Atma Luhur Pangkalpinang, scholarships are offered not only to students who have excellent academic achievements but also for those with special abilities in other fields, such as for outstanding athletes. The number of classifications gives top management a hard time to decide who will receive the scholarship. The difficulty lies on the lack of clear criteria in awarding the scholarships either from campus or from the government based on both academic and non academic achievements. This study presents several criteria that can be used to determine which students deserve to receive which scholarship. This study uses the Analytical Hierarchy Process (AHP) as a model of decision making in determining scholarship recipients. The results of data processing tools with AHP and Expert Choice 2000 indicate that the scholarship (Improved Academic Achievement or PPA) is the most popular fellowship that reaches 23.3%, followed by student’s achievements by 22.3%,. The third is a scholarship Student aid Study (BBM) that reaches 21.5%. While the most important criteria according to the expert respondents is on academic achievement that reaches 50.3%.Keywords: scholarship, academic and non academic achievement, Analytical Hierarchy Proces. Abtrak. Di STMIK Atma Luhur Pangkalpinang, beasiswa tidak hanya untuk mahasiswa yang mempunyai kemampuan akademik sangat baik, namun juga untuk mahasiswa yang mempunyai kemampuan istimewa lainnya seperti atlet berprestasi. Banyaknya klasifikasi beasiswa membuat manajemen puncak sebagai penentu akhir kepada siapa beasiswa akan diberikan cukup kesulitan. Penelitian ini menyajikan beberapa kriteria yang dapat digunakan untuk menentukan mahasiswa dengan kategori seperti apa yang paling pantas menerima beasiswa – beasiswa tersebut. Penelitian ini menggunakan Analytical Hierarchy Process (AHP) sebagai model pengambilan keputusan dalam menemtukan mahasiswa penerima beasiswa. Hasil pengolahan data dengan AHP dan tools Expert Choice 2000 menunjukkan bahwa beasiswa (Peningkatan Prestasi Akademik (PPA) adalah beasiswa yang paling diminati dengan bobot mencapai 23,3%, selanjutnya adalah beasiswa mahasiswa berprestasi dengan bobot 22,3%, dan peringkat ketiga adalah beasiswa Bantuan Belajar Mahasiswa (BBM) dengan bobot mencapai 21,5%. Sedangkan kriteria paling penting menurut para responden ahli adalah prestasi akademik dengan bobot mencapai 50,3%. Kata Kunci: beasiswa, beasiswa berbasis akademik, beasiswa non akademik, Analytical Hierarchy Process.